The Moderation Role Of Transformational Leadership Between Human Capital And Organizational Innovation In Abu Dhabi Government - Alseiari, Abdulrahman Mohammed Suliman; Sidek, Safiah; Al-Shami, Samer Ali Hussein (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Transformational leadership with human capital, and innovation are key success factors for modern organizations. Effective leadership style that encourages innovation among human resources will add competitve advantage to the organization. The aim of this study is to examine the moderation role of transformational leadership between human capital and organizational innovation. To achieve this aim, this study adopted quantitative and a survey by collecting data from employees of public sector in Abu Dhabi. Descriptive and inferential statistics was used to analyses the quantitative data. The result of this study shows transformational leadership moderates the association between human capital and organizational innovation. This study is one of the first, to the best of the researcher’s knowledge to test moderation tole of transformation leadership in UAE. Therefore, the author recommends the leaders in public organizations in UAE to focus on the factors associated with human capital in particular knowledge, skill, and attitude of employees in order to improve the level of innovation in their organization. The outcome of this study revealed that, the vision of transformation leader is very important to achieve competitive advantage for organizations in UAE through encouraging human capital towards innovation in work and business. Thus, it is highly recommended to assign transformational leaders in UAE organizations to enhance innovation within workplace as one of the main characteristics of transformation leaders is supporting human capital towards innovation.